STUDI EVALUASI PENILAIAN KOGNITIF DENGAN TEKNIK TES PILIHAN GANDA BERBANTUAN APLIKASI EDMODO PADA PEMBELAJARAN PPKN KELAS X DI SMA NEGERI 1 NGEMPLAK - Noviyani; Wijianto; Winarno (Asosiasi PPKn, 2019)
This research was conducted with the aim to find out the process and constraints faced by teachers in implementing cognitive assessment with multiple choice test technique by Edmodo Application on PPKn learning at class X SMA Negeri 1 Ngemplak. This study uses a qualitative research approach with a qualitative descriptive approach. Data sources are obtained from informants, places, events and documents. The sampling technique used was purposive sampling with data collection techniques in the form of interviews, observation and document analysis. To obtain data validity, data triangulation and triangulation methods are used. While the data analysis technique uses an interactive analysis model consisting of data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the discussion, it can be concluded that the process of implementing cognitive assessment with multiple-choice test techniques based on Edmodo application includes 4 (four) stages, that is preparation, construction of the question instruments into Edmodo application, implementation, and processing of assessment results. However, the evaluation procedure is not fully implemented. In addition there are also obstacles faced by teachers including technical and non-technical constraints. Technical constraints Technical constraints include, a. Availability of computer devices; b. internet network access; c. preparation of multiple choice questions into Edmodo application; and d. students have difficulty to accessing Edmodo account.. While non-technical constraints include, a. class is not conducive and b. behavior of students.   Full Paper